The Relationship between CEO Compensation and Firm Performance in the Banking Sector of Bangladesh - Harun, Md. Yousuf; Hamid, Md. Kaysher (AIUB Journal of Business and Economics, 2016)
To study the pay-performance relationship, 24 commercial banks listed with DSE have been selected for 2004-15. Total annual compensation paid to CEO represents the CEO compensation (CEOCOM) and return on assets (ROA), net interest margin (NIM), capital adequacy ratio (CAR), loan-deposit ratio (LDR), classified loan ratio (CLR), and price per share (PPS) are used as the performance indicators. CEOCOM has shown an increasing trend over the years with average YOY growth of 12.92% and CAGR of 12.73%. A strong positive correlation of CAR and a strong negative correlation of PPS are observed with CEOCOM. Besides, ROA, NIM, and LDR have a weak positive and CLR have a weak negative correlation with CEOCOM. Regression result shows a strong correlation and high explanatory power of the independent variables against CEOCOM. The model is also found statistically significant and free of multicollinearity. In addition, ROA, CLR, and PPS have shown negative and NIM, CAR and LDR have illustrated positive coefficients with CEOCOM. Except LDR (significant at 86.1%), all the variables are significant at 95% confidence level. Therefore, this research concludes a significant relationship between CEO compensation and firm performance.